2019
DOI: 10.1167/iovs.18-25272
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Photopic Negative Response and Retinal Ganglion Cell Topography

Abstract: PURPOSE. To assess the topographic relationship between the photopic negative response (PhNR) and retinal ganglion cell distribution in healthy individuals. METHOD. Data was recorded from 16 healthy participants. The amplitude of PhNRs obtained in response to focal long duration (250 ms) and brief flash (5 ms), red (660 nm) on blue (469 nm) stimuli of increasing size (58-full field) were measured. The number of retinal ganglion cell receptive fields (RGCf) in each stimulus area was established from the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(76 reference statements)
0
7
0
1
Order By: Relevance
“…Our data matches studies using different experimental glaucoma models, which have also shown a decrease in PhNR amplitudes in ocular hypertensive monkeys and rabbits [ 17 , 38 ]. In addition, the diagnostic utility of the PhNR for patients who are glaucoma suspects has been demonstrated in multiple studies [ 10 , 38 , 41 , 50 , 51 ]. While the pattern ERG has also been suggested as a preclinical diagnostic for glaucoma and other RGC-related diseases, the PhNR has the advantage of not requiring refractive correction [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data matches studies using different experimental glaucoma models, which have also shown a decrease in PhNR amplitudes in ocular hypertensive monkeys and rabbits [ 17 , 38 ]. In addition, the diagnostic utility of the PhNR for patients who are glaucoma suspects has been demonstrated in multiple studies [ 10 , 38 , 41 , 50 , 51 ]. While the pattern ERG has also been suggested as a preclinical diagnostic for glaucoma and other RGC-related diseases, the PhNR has the advantage of not requiring refractive correction [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 These models of Drasdo et al 22 and Watson 23 have been used subsequently to determine the number of RGC-RFs underlying stimuli at select retinal locations. 24,25 Whilst average histological models have been widely used to estimate RGC numbers in individual observers, their use is markedly limited by the relative inability to account for interindividual variations in RGC density secondary to physiological and/or pathological processes. Other techniques utilising measures of function or structure attempt to overcome such limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Curcio and Allen's RGC‐CB data 18 was used in the development of two theoretical equations that model RGC‐RF density in the human visual field 22,23 . These models of Drasdo et al 22 and Watson 23 have been used subsequently to determine the number of RGC‐RFs underlying stimuli at select retinal locations 24,25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photopic negative response (PhNR) in full filed electroretinogram is a marker of retinal ganglion cell activity. [ 5 ] Loss of retinal ganglion cells is an integral aspect of diabetic retinal neuropathy and it was imperative that PhNR would have been studied in detail prior to the present study. However, the present study adds value to the existing body of literature by using both broadband (white on white) and monochromatic (red on blue and blue on yellow) PhNR and correlating them with various stages of diabetic retinopathy.…”
mentioning
confidence: 99%